A Literature of "Truth": Writing by Gay Men in East Germany - Denis M. Sweet (Studies in 20th & 21st Century Literature, 1998)
In the last few years of its existence, the East German socialist state had initiated a campaign of tolerance and integration of its homosexuals into socialist society that seemed to cast the GDR in a more progressive light than West Germany. Breaking with the taboos of the previous era, gay literary works were allowed to be published for the first time. These works were in genres (a diary, representative interviews, a confession) that suggested unmitigated truth. Yet a closer analysis reveals them to be works not so much of 'truth' as of compromise and cooptation by a state policy of containment.
Keywords: Truth; gay; men; East Germany; East German; DDR; socialist state; tolerance; integration; homosexuals; socialist society; GDR; progressive; West Germany; taboo; gay literary works; genres; diary; representative interviews; confession; compromise; cooptation; state policy of containment